STUDI LITERATUR: STRATEGI BIMBINGAN DAN KONSELING ISLAM DALAM MENGATASI BERBAGAI GANGGUAN KESEHATAN MENTAL PADA REMAJA - Rizqi, Fina Auliya; Nur Khayati, Sifa (MUHAFADZAH: Jurnal Ilmiah Bimbingan dan Konseling Islam, 2025)
This study aims to analyze various strategies of Islamic Guidance and Counseling (BKI) in addressing mental health problems among adolescents through a literature review method. The data were obtained from scientific journals, academic articles, and books discussing Islamic counseling interventions and adolescent mental health. Previous studies show that adolescents often experience stress, anxiety, mild depression, decreased motivation, and adjustment difficulties influenced by social, academic, and psychological factors. The findings reveal that effective BKI strategies include dhikr, prayer, tazkiyatun nafs, selfreflection (muhasabah), Sayyidul Istighfar, faith strengthening, and both individual and group counseling based on Islamic values. These interventions have been shown to reduce anxiety, enhance self-control, improve resilience, foster meaning in life, and promote spiritual calmness among adolescents. The study concludes that Islamic Guidance and Counseling contributes significantly as both a preventive and curative approach to improving adolescent mental health. Nevertheless, this research is limited by its reliance on secondary sources and predominantly qualitative data, indicating the need for future field studies to compare the effectiveness of various BKI strategies.